Conductive extracellular matrix derived/chitosan methacrylate/ graphene oxide-pegylated hybrid hydrogel for cell expansion - Jaramillo, Valentina; Arévalo, Daniel Felipe; González-Hernández, Martin; Cortés, María T.; Perdomo-Arciniegas, Ana María; Cruz, Juan C.; Muñoz-Camargo, Carolina (Frontiers in Bioengineering and Biotechnology, 2024)
In the rapidly evolving field of biomedical engineering, particularly within the realms of tissue engineering and regenerative medicine, electrical stimulation has emerged as a cornerstone technique. It facilitates cell growth, proliferation, and differentiation, thereby advancing the development of accurate tissue models and enhancing drug testing methodologies. Central to this advancement are conductive hydrogels, which enable the conduction of micro-currents in 3D in vitro cultures. The integration of high-electroconductive nanomaterials, such as graphene oxide (GO), into hydrogels has revolutionized their mechanical and conductivity properties. Here, we introduce a novel electrostimulation assay utilizing a hybrid hydrogel composed of methacryloyl-modified SIS dECM (SISMA), chitosan methacrylate (ChiMA) and GO-polyethylene glycol (GO-PEG) in a 3D in vitro culture within a hypoxic environment of umbilical cord blood cells (UCBCs). Results not only demonstrate significant cell proliferation within 3D constructs exposed to micro-currents and early growth factors but also highlight the hybrid hydrogel's physiochemical prowess through comprehensive rheological, morphological and conductivity analyses. Further experiments will focus on identifying the regulatory pathways of cells subjected to electrical stimulation.